Penilaian Sejawat dalam Keterampilan Dasar Mengajar Memberikan Penguatan pada Mata Kuliah Microteaching: Improving Basic Teaching Skills Provides Strengthening Through Peer Assessment in Microteaching Courses - Marlina; Siti Rahmah; Fathony, Muhammad Hafiz (Jurnal Ilmiah Edukatif, 2024)
This research aims describe the application of peer assessment in providing reinforcement to the PGSD Microteaching course at at Nahdlatul Ulama University, South Kalimantan, for the academic year 2023-2024. The research was conducted using a qualitative descriptive method. The subjects in this research were students of Class 6A of the PGSD Study Program at Nahdlatul Ulama University, South Kalimantan, for the academic year 2023-2024. The research instrument used was an observation sheet of reinforcement skills. The results of this research show that the average value of student observations using reinforcement techniques is in the good category. It can be concluded that peer assessment can be used as an alternative to enhance basic teaching skills in Microteaching courses, especially in reinforcement skills.